On the Ethics of Vaccine Nationalism: The Case for the Fair Priority for Residents Framework. Issue 4 (2021) - Emanuel, Ezekiel J.; Buchanan, Allen; Chan, Shuk Ying; Fabre, Cécile; Halliday, Daniel; Leland, R. J.; Luna, Florencia; McCoy, Matthew S.; Norheim, Ole F.; Schaefer, G. Owen; Tan, Kok-Chor; Wellman, Christopher Heath
Abstract: COVID-19 vaccines are likely to be scarce for years to come. Many countries, from India to the U.K., have demonstrated vaccine nationalism. What are the ethical limits to this vaccine nationalism? Neither extreme nationalism nor extreme cosmopolitanism is ethically justifiable. Instead, we propose the fair priority for residents (FPR) framework, in which governments can retain COVID-19 vaccine doses for their residents only to the extent that they are needed to maintain a noncrisis level of mortality while they are implementing reasonable public health interventions. Practically, a noncrisis level of mortality is that experienced during a bad influenza season, which society considers an acceptable background risk. Governments take action to limit mortality from influenza, but there is no emergency that includes severe lockdowns. This "flu-risk standard" is a nonarbitrary and generally accepted heuristic. Mortality above the flu-risk standard justifies greater governmental interventions, including retaining vaccines for a country's own citizens over global need. The precise level of vaccination needed to meet the flu-risk standard will depend upon empirical factors related to the pandemic. This links the ethical principles to the scientific data emerging from the emergency. Thus, the FPR framework recognizes that governments should prioritize procuring vaccines for their country when doing so is necessary to reduce mortality to noncrisis flu-like levels. But after that, a government is obligated to do its part to share vaccines to reduce risks of mortality for people in other countries. We consider and reject objections to the FPR framework based on a country: (1) having developed a vaccine, (2) raising taxes to pay for vaccine research and purchase, (3) wanting to eliminate economic and social burdens, and (4) being ineffective in combating COVID-19 through public health interventions.